Diverging response patterns of terrestrial and aquatic species to hydromorphological restoration. Issue 1 (13th September 2018) - Pilotto, Francesca; Tonkin, Jonathan D.; Januschke, Kathrin; Lorenz, Armin W.; Jourdan, Jonas; Sundermann, Andrea; Hering, Daniel; Stoll, Stefan; Haase, Peter
Abstract: Although experiences with ecological restoration continue to accumulate, the effectiveness of restoration for biota remains debated. We complemented a traditional taxonomic analysis approach with information on 56 species traits to uncover the responses of 3 aquatic (fish, macroinvertebrates, macrophytes) and 2 terrestrial (carabid beetles, floodplain vegetation) biotic groups to 43 hydromorphological river restoration projects in Germany. All taxonomic groups responded positively to restoration, as shown by increased taxonomic richness (10–164%) and trait diversity (habitat, dispersal and mobility, size, form, life history, and feeding groups) (15–120%). Responses, however, were stronger for terrestrial than aquatic biota, and, contrary to our expectation, taxonomic responses were stronger than those of traits. Nevertheless, trait analysis provided mechanistic insights into the drivers of community change following restoration. Trait analysis for terrestrial biota indicated restoration success was likely enhanced by lateral connectivity and reestablishment of dynamic processes in the floodplain. The weaker response of aquatic biota suggests recovery was hindered by the persistence of stressors in the aquatic environment, such as degraded water quality, dispersal constraints, and insufficient hydromorphological change. Therefore, river restoration requires combined local‐ and regional‐scale approaches to maximize the response of both aquatic and terrestrial organisms. Due to the contrasting responses of aquatic and terrestrial biota, the planning and assessment of river restoration outcomes should consider effects on both components of riverine landscapes. Abstract : Article impact statement : River restoration increases taxonomic richness and trait diversity of terrestrial biotic groups and to a lesser extent aquatic groups Abstract : Patrones Divergentes de Respuesta de las Especies Terrestres y Acuáticas ante la Restauración Hidromorfológica Resumen: Aunque se siguen acumulando las experiencias con respecto a la restauración ecológica, la efectividad de la restauración para la biota todavía está en discusión. Complementamos un método de análisis taxonómico tradicional con información sobre 56 rasgos de especies para descubrir las respuestas de tres grupos bióticos acuáticos (peces, macroinvertebrados, macrofitas) y dos grupos bióticos terrestres (escarabajos carábidos, vegetación de planicies inundables) ante 43 proyectos de restauración hidromorfológica de ríos en Alemania. Todos los grupos taxonómicos respondieron positivamente a la restauración, como lo demostró el incremento en la riqueza taxonómica (10‐164%) y en la diversidad de rasgos (hábitat, dispersión y movilidad, tamaño, forma, historia de vida, y grupos de alimentación) (15‐120%). Sin embargo, las respuestas fueron más fuertes para la biota terrestre que para la acuática, y, contrario a nuestra expectativa, las respuestas taxonómicas fueron más fuertes que las respuestas de los rasgos. Aun así, el análisis de los rasgos proporcionó conocimiento mecánico sobre los conductores del cambio comunitario tras la restauración. El análisis de los rasgos para la biota terrestre indicó que el éxito de la restauración probablemente estaba mejorado por la conectividad y el restablecimiento de los procesos dinámicos en la planicie inundable. La respuesta más débil de la biota acuática sugiere que la recuperación estuvo obstaculizada por la persistencia de las fuentes de estrés en el ambiente acuático, como la calidad degrada del agua, las restricciones de dispersión, y el cambio hidromorfológico insuficiente. Por lo tanto, la restauración de ríos requiere estrategias de restauración de ríos locales y regionales combinadas para maximizar la respuesta tanto de los organismos terrestres como de los acuáticos. Debido a las respuestas contrastantes entre la biota terrestre y la acuática, la planeación y la evaluación de los resultados de la restauración de ríos debería considerar los efectos sobre ambos componentes de los paisajes ribereños.